Analisis Yuridis Pengaruh Cyberbullying terhadap Publik Figur - Kenny Ferris Ave (Jurnal Hukum Lex Generalis, 2024)
The advancement of technology and communication is currently very advanced. The advancement of communication technology can have good or bad impacts depending on the people who use it. One of the bad impacts is the emergence of cyberbullying. In this case, the target victims of cyberbullying are usually public figures who work in the entertainment world. The purpose of this study is for readers to know how cyberbullying can affect the daily lives of its victims, especially public figures, and how to enforce the law against cyberbullying. The legal theory that will be used in this study is the theory of Legal Utilitarianism (Utilitarianism Legal Theory).